Mechanical engineering design - Ugural, A. C.; Chon, Yonjin; Ugural, Errol A. (CRC Press, 2021)
"Mechanical engineering design, third edition strikes a balance between theory and application, and prepares students for more advanced study or professional practice. Updated throughout, it outlines basic concepts and provides the necessary theory to gain insight into mechanics with numerical methods in design. Divided into three sections, the text presents background topics, addresses failure prevention across a variety of machine elements, and covers the design of machine components as well as entire machines. Optional sections treating special and advanced topics are also included. Features : Places a strong emphasis on the fundamentals of mechanics of materials as they relate to the study of mechanical design. Furnishes material selection charts and tables as an aid for specific utilizations. Includes numerous practical case studies of various components and machines. Covers applied finite element analysis in design, offering this useful tool for computer-oriented examples. Addresses the ABET design criteria in a systematic manner. Presents independent chapters that can be studied in any order. Introduces optional MATLAB solutions tied to the book and student learning resources. Mechanical engineering design, third edition allows students to gain a grasp of the fundamentals of machine design and the ability to apply these fundamentals to various new engineering problems".